Criminal Liability by the Pharmaceutical Industry on the Use of Precursors for Illicit Narcotics in Indonesia: A Review - Haksama, Setya; Dimjati Lusno, M. Farid; Setyowati, Anggi; Wulandari, Anis; Nugroho, Bastianto; Roesli, M.; Hidayat, M.; Rudianto, Ebit; Khan, M. Mahmud; Sriram, Shyamkumar; Shedysni, Syahrania Naura; Hafidzudin Farid, M. Rifqo; et al. (International Journal of Criminology and Sociology, 2022)
Purpose of the study: the aim of this study was to review the law enforcement regarding precursors for manufacturing narcotic drugs in Indonesia. Methodology: This study used normative legal research, which used the law as positive norms that regulates human life, it used several approaches, that were examined various rules of law as well as case approach. The data was collected through literature studies. Main Findings and Applications of this Study: In Indonesia, the highest regulation in the crime of narcotics is based on the Law of the Republic of Indonesia Number 35 of 2009 concerning Narcotics. The aims of this regulation are to protect the public from precursor’s abuse to narcotics; preventing and eradicating illicit traffic of precursors of narcotics; as well as preventing leaks and irregularities. Novelty: The pharmaceutical industry as a legal entity has the possibility to conduct criminal action such as using precursor for illicit narcotic and if it is proved to be in violation, it will be punished. Furthermore, it requires integration by involving national, regional and international coordination to prevent this criminal liability